If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5n + -7) = 9 Reorder the terms: 3(-7 + 5n) = 9 (-7 * 3 + 5n * 3) = 9 (-21 + 15n) = 9 Solving -21 + 15n = 9 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 15n = 9 + 21 Combine like terms: -21 + 21 = 0 0 + 15n = 9 + 21 15n = 9 + 21 Combine like terms: 9 + 21 = 30 15n = 30 Divide each side by '15'. n = 2 Simplifying n = 2
| =10a+20b | | 5(n+6)=10 | | (2w^7x^5/3z^7)^3 | | -5v+25=-3(v-9) | | 3z^3-8z^2=0 | | -20=4(u-6)-8u | | 6-4.5-6= | | 9z^3-64z=0 | | 2/3t-16=62 | | 3(a+14)=6(2a+3) | | -19=-3+4w | | 6x-2k+8=x+5 | | 8n^2=6 | | 294=18-y | | 35y^2-9y+3=0 | | 284=18-y | | 2m^2+27m-4=0 | | 2n+3=4n-7 | | 1.75x=4.2 | | 6n+12=20 | | 2m^2=10-2m | | (n+3)(2n+3)=0 | | 10+9x=10+x | | x^2+y^2+2*x+14*y-15=0 | | 2n^2=105-11n | | 10x-17=2x+10 | | 5.7-6/12 | | x(a-6b)=3m(x-c) | | 0=-16t+40t-84 | | 26-m=76 | | g(x)=x^5-9x^3 | | 6(15-3x)=120 |